2023
DOI: 10.3389/fphys.2022.1063956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased protein intake and exogenous ketosis on body composition, energy expenditure and exercise capacity during a hypocaloric diet in recreational female athletes

Abstract: Introduction: Since low body weight is an important determinant of success in many sports such as gymnastics, martial arts and figure skating, athletes can benefit from effective weight loss strategies that preserve muscle mass and athletic performance. The present study investigates the effects of increased protein intake and exogenous ketosis on body composition, energy expenditure, exercise capacity, and perceptions of appetite and well-being during a hypocaloric diet in females.Methods: Thirty-two female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In the present CETUS study, participants were sedentary, and this may explain why no difference in the levels of GDF-15 was observed (i.e., the magnitude of the stress response was much lower compared with that observed during intensive training). A study in recreational female athletes, who were placed on a diet that restricted calories by 30% for four weeks and consumed a ketone supplement before every meal, also reported no statistically significant changes in GDF-15 [ 27 ]. That study also reported no changes in the circulating levels of ghrelin and leptin [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present CETUS study, participants were sedentary, and this may explain why no difference in the levels of GDF-15 was observed (i.e., the magnitude of the stress response was much lower compared with that observed during intensive training). A study in recreational female athletes, who were placed on a diet that restricted calories by 30% for four weeks and consumed a ketone supplement before every meal, also reported no statistically significant changes in GDF-15 [ 27 ]. That study also reported no changes in the circulating levels of ghrelin and leptin [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in recreational female athletes, who were placed on a diet that restricted calories by 30% for four weeks and consumed a ketone supplement before every meal, also reported no statistically significant changes in GDF-15 [ 27 ]. That study also reported no changes in the circulating levels of ghrelin and leptin [ 27 ]. It is pertinent to note here that another CETUS study also found no significant effect of acute ketone supplementation on the circulating levels of leptin [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation